Increasing dissolved oxygen in water enhances the flooding tolerance of Carya illinoinensis - Chen, Xue; Wang, Xia; Hu, Haibo; Wu, Chaoming; Zhu, Li (Frontiers in Plant Science, 2026)
Flood-induced seedling mortality along riverbanks is a global issue, primarily caused by oxygen deficiency and associated secondary stresses during submergence. To address this problem, our study introduced an innovative approach by enhancing dissolved oxygen (DO) in floodwater to alleviate flooding stress. We conducted a pot experiment using one-year-old seedlings of two Carya illinoinensis cultivars, ‘Mahan’ and ‘Pawnee’, under three treatments: control (CK), high-oxygen flooding (HO), and low-oxygen flooding (LO). Morphological, growth, and physiological responses of both cultivars were systematically evaluated to comprehensively assess their flooding tolerance. The results demonstrated that aeration significantly mitigated both physiological damage and growth inhibition caused by flooding. After 60 days of flooding, compared with the LO treatment, the HO treatment reduced the leaf injury rate (by 11.11% in ‘Mahan’ and 0% in ‘Pawnee’) and the injury index by 26.43–31.75% in both cultivars. It also increased the growth rate in plant height (GRH) by 18.18–166.67%, total biomass (TB) by 15.69–18.17%, and root-to-shoot ratio (RSR) by 18.18–34.94%. Moreover, the HO treatment led to reductions in malondialdehyde (MDA) content by 7.55–7.87%, soluble protein (SP) content by 2.14–20.50%, and activities of superoxide dismutase (SOD) and catalase (CAT) by 16.86–17.16% and 17.20–23.73%, respectively. Membership function analysis further revealed that plants in the HO treatment exhibited superior overall stress resistance compared to those in the LO treatment, with the resistance ranking as follows: ‘Mahan’-HO > ‘Mahan’-LO > ‘Pawnee’-HO > ‘Pawnee’-LO. In summary, this study explores how elevated dissolved oxygen alleviates key flood stress symptoms, thus providing a theoretical foundation for flood-resistant management of C. illinoinensis in the Yangtze River Basin and a novel intervention framework for other terrestrial plants facing periodic flooding.